Moneys Financial Record Application Design for Mobile-Based Students - Dwiwahyu, Anisah Nurdina; Wardani, Indri Eka; Wiranatakusuma, Dimas Bagus (Universitas Muhammadiyah Yogyakarta, 2023)
Students who are in the transition period from youth to adulthood still do not have a stable emotional level that can manage and handle money. It takes careful preparation to handle funds so that the money earned can be used according to its purpose. We now live in the mobile era, therefore we need a mobile application. The design of this application begins with the identification of information needs and the presence of attractive and complete features in the application that make students interested in using it. The research findings show that students want a live app with features to track their expenses, income, and budget. Using Android as a foundation, the Moneysv app can be created. The mobile-based Moneysv Financial Management application uses the Java programming language, Notepad++ application software, and Android SDK, which types the program code and application logic. SQLite is used to create the database structure. With the Black Box testing approach, system testing procedures can be performed.